2019
DOI: 10.3390/atmos10120734
|View full text |Cite
|
Sign up to set email alerts
|

A Novel Approach for Water Conservation and Plume Abatement in Mechanical Draft Cooling Towers

Abstract: While the visible plume from a cooling tower is not a pollutant, it can affect the surrounding environment. Moreover, the accompanied evaporation loss has a great potential for wastewater recovery. In the present study, a novel coupling technology for water conservation and plume abatement was proposed, and its feasibility was verified by using thermodynamic analysis. A surface-type heat exchanger was designed and a thermodynamic calculation model was established. Next, based on the principle of “no plume,” th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Recently Wang et al [151] evaluated the plume abatement and water conservation performances of the Air2Air TM heat exchanger. They found that water savings increased significantly under ambient conditions of low temperature and high RH.…”
Section: Water Conservation and Recoverymentioning
confidence: 99%
See 1 more Smart Citation
“…Recently Wang et al [151] evaluated the plume abatement and water conservation performances of the Air2Air TM heat exchanger. They found that water savings increased significantly under ambient conditions of low temperature and high RH.…”
Section: Water Conservation and Recoverymentioning
confidence: 99%
“…The atmosphere can be either stable ( N 2 > 0 ), neutral ( N 2 = 0 ) or unstable ( N 2 < 0). [144,148,149] and solar collectors [150] HVAC cooling towers, suitable for high relative humidity Enhanced mixing using static and non-static mixers Deflecting surfaces [21,71,129], vortex generators [123,124] and stirring mixing devices [107] Cooling towers (including back-to-back towers) with Level 2 plume abatement criterion [9] Coaxial plume mixing Hybrid (crossflow) towers [57,79,80,93] Cooling towers designed with Level 1 plume abatement criterion [9] Cooling the hot, humid air Water vapor channel [114], thermosyphon system [99], air-toair heat exchangers [58,94,151] Preferred in large back-to-back towers and in arid regions; good functionality even in freezing weather conditions (condensed) and dry (uncondensed) plumes under different atmospheric conditions. Later Wigley [152] included the dynamics of droplet growth in the condensation phase.…”
Section: Analytical Modelsmentioning
confidence: 99%